Downregulation of DJ-1 Fails to Protect Mitochondrial Complex I Subunit NDUFS3 in the Testes and Contributes to the Asthenozoospermia - Yupeng Wang; Yi Sun; Xin Zhao; Renpei Yuan; Hui Jiang; Xiaoping Pu (Mediators of Inflammation)
Asthenozoospermia (AS), an important cause of male infertility, is characterized by reduced sperm motility. Among the aetiologies of AS, inflammation seems to be the main cause. DJ-1, a conserved protein product of the PARK7 gene, is associated with male infertility and plays a role in oxidative stress and inflammation. Although our previous studies showed that a reduction in DJ-1 was accompanied by mitochondrial dysfunction in the sperm of patients with AS, the specific mechanism underlying this association remained unclear. In this study, we found that compared to the patients without AS, the expression of mitochondrial protein nicotinamide adenine dinucleotide dehydrogenase (ubiquinone) Fe-S protein 3 (NDUFS3) was also significantly decreased in the sperm of patients with AS. Similarly, decreased expression of DJ-1 and NDUFS3 and reduced mitochondria complex I activity were evident in a rat model of AS. Moreover, we showed that the interaction between DJ-1 and NDUFS3 in rat testes was weakened by ORN treatment. These results suggest that the impaired mitochondrial activity could be due to the broken interaction between DJ-1 and NDUFS3 and that downregulation of DJ-1 in sperm and testes contributes to AS pathogenesis.